Respuestas
Respuesta dada por:
1
Elevando al cubo
(x + y)^3 = 1
x^3 + 3x^2y + 3xy^2 + y^3 = 1
D xy = 1
x = 1/y
y = 1/x
Reemplazando valores
x^3 + 3(1/y)^2y + 3x(1/x)^2 + y^3 = 1
Efectuando
x^3 + 3y + 3x + y^3 = 1
x^3 + y^3 + 3(x + y) = 1
x^3 + y^3 + 3(1) = 1
x^3 + y^3 = 1 - 3
x^3 + y^3 = - 2 RESULTADO FINAL
(x + y)^3 = 1
x^3 + 3x^2y + 3xy^2 + y^3 = 1
D xy = 1
x = 1/y
y = 1/x
Reemplazando valores
x^3 + 3(1/y)^2y + 3x(1/x)^2 + y^3 = 1
Efectuando
x^3 + 3y + 3x + y^3 = 1
x^3 + y^3 + 3(x + y) = 1
x^3 + y^3 + 3(1) = 1
x^3 + y^3 = 1 - 3
x^3 + y^3 = - 2 RESULTADO FINAL
Preguntas similares
hace 9 años
hace 9 años
hace 9 años